A comparison between the recent financial crisis of 2008 and the crisis of 1999 in the Athens Stock Market. (1st January 2012) - Maligkris, Anastasios; Koulakiotis, Athanasios; Kiohos, Apostolos
This paper examines the two financial crises of the Athens Stock Market during the last decade, in order to help investors and academics to understand better its attitude in periods of crises. In this analysis, it was employed a Quandt-Andrews Test, a GJR-GARCH model with two diagnostic tests and a BDS independence test. The results have showed that in the most recent crisis the asymmetries were almost similar as they were in the crisis of 1999, however, the magnitude of volatility in 2008, which was specifically created by big negative shocks, was higher. Contrasting the above results with the estimation of the middle period, it was found that in the middle period there was a positive size bias, while on the contrary in the periods of crises there was a negative one. Finally, we point out the existence of chaotic autocorrelations in both crises, affecting the ASE index non-linearly.